The state in modern society : new directions in political sociology - King, Roger (Macmillan, 1986)
This is an up-to-date textbook which takes fully into account recent developments in political sociology. Taking as its starting point the fragmentation of the discipline, it covers a wide range of new issues and debates as well as the more traditional concerns of the subject.